Journey Through Egypt: From the Collection of the Ruler of Sharjah/ (3QMdI YHQ eUQ(B: (3ef ebJfjGJ MVQI UGMH GdSeh MGce GdTGQbIs - Qasimi Collection ((3OGFQI GdKbGaI h GdEYdGe, McheI GdTGQbI; s, 2013)
Collection of David Roberts' Orientalist drawings and sketches. Text: dr. Abdulkarim Alsayed.
English; Arabic
Keywords: Drawings; N5198-5299 Visual Arts- Private collections and collectors; Orientalist Collection; Egypt